DESAIN PEMBELAJARAN GARIS BAGI SUDUT DENGAN PENDEKATAN MATEMATIKA REALISTIK - Bagus Ardi Saputro; Sumarni Sumarni (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
The objective of this research is to find the phenomenon and design the learning with the characteristics of realistic mathematical approach and the scientific approach for the procedure of constructing the line for the angle. This research is research and development which still on the table experiment stage that choose the topic stage, subject matter, concept, and scenario in relevant situation type with the concept. In the development stage obtained the first stage instructional design to determining the seat of advertising tower founded crossroads of three roads selected as a context for learning that leads students beginning in accordance with the characteristics of realistic mathematics approach.the initial design of the first stage of research development was implementation, by tested to three students of mathematics education level II semester 3 at one of the private university on December 2017. The result of design instructional tasted show that begins with the context of establishing advertising tower at the intersection of three streets can be used as an alternative design of line learning for angles. This design is in accordance with the characteristics of a realistic mathematical approach and will be more effective if students are adept at using GeoGebra and using the software in the learning process.